Aproveitamento de resíduo mineral da exploração de esmeraldas em massa cerâmica: caracterização mineralógica e química, formulação e potencial tecnológico - Gentil, Talita Fernanda Carvalho (2024)
The exploitation of emerald deposits in the northeastern region of Bahia is carried out in an unregulated manner in mining areas, often without prior geological studies or specific technical supervision during the mineral extraction process. This practice results in significant environmental liabilities for the region. The present study focuses on identifying viable applications for the waste generated from this mining activity, with emphasis on the construction and ceramics sectors. The aim is to add value to such waste, specifically the mineral by-product from emerald mining, by incorporating it as a component in ceramics for the production of blocks, bricks, special tiles, and other products. The integration of this waste into sustainable production processes represents a significant advancement towards a more balanced and efficient approach in the mining sector. Thus, with the goal of combining experience and technical information to contribute to sustainable development and offer significant benefits to the construction sector and society, this research investigates the incorporation of waste from emerald mining into ceramic matrices, varying the incorporation levels at 10, 20, 30, 40, and 50 %. The study encompasses evaluations of the chemical, mineralogical, and thermal compositions, as well as the behavior of gloss intensity, optical, physical, and mechanical properties. The raw materials were characterized using analytical techniques, including X-ray fluorescence, X-ray diffraction, gloss intensity loss tests, and colorimetric analyses. The test specimens were formed and subjected to firing at different temperatures (850, 900, 1000, 1100, and 1200 °C) with a 1-hour isotherm and a heating rate of 10 °C/min. Several technological tests were conducted, including Linear Firing Shrinkage, Loss on Ignition, Water Absorption, Apparent Porosity, and Apparent Specific Mass. The results revealed that the incorporation of emerald mining waste into ceramic mass produced a final product with technological properties that meet the technical standards for use in the construction and ceramics sectors. Notably, incorporation levels between 10 % and 20 % demonstrated acceptable results